Analisis Faktor yang Berhubungan dengan Perilaku Promosi Kesehatan Masyarakat di Masa Pandemi COVID-19 - Yellyanda Yellyanda; Bettywati E. Tumanggor (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze factors related to public health promotion behavior during the COVID-19 pandemic. This research method is observational analytic using a cross-sectional design. The results showed that the majority of respondents had good knowledge 64.85, had a positive attitude 67.65, had a high motivation of 88.6%, had high family support 84.8%, and had good behavior of 75.2%. The chi-square test shows that health promotion behavior is related to knowledge (P-value 0.003), attitude (P-value 0.001), and family support (P-value 0.004), while motivation is not related (P-value 0.215). In conclusion, health promotion behavior in preventing the spread of COVID-19 is proven to be related to sound knowledge, positive attitudes, and high family support but not motivation. Keywords: COVID-19, Behavior, Health Promotion